A quality comparison of protein crystals grown under containerless conditions generated by diamagnetic levitation, silicone oil and agarose gel. (8th October 2013) - Cao, Hui‐Ling; Sun, Li‐Hua; Li, Jian; Tang, Lin; Lu, Hui‐Meng; Guo, Yun‐Zhu; He, Jin; Liu, Yong‐Ming; Xie, Xu‐Zhuo; Shen, He‐Fang; Zhang, Chen‐Yan; Guo, Wei‐Hong; et al.
<x xml:space="preserve">Abstract</x> High‐quality crystals are key to obtaining accurate three‐dimensional structures of proteins using X‐ray diffraction techniques. However, obtaining such protein crystals is often a challenge. Several containerless crystallization techniques have been reported to have the ability to improve crystal quality, but it is unknown which is the most favourable way to grow high‐quality protein crystals. In this paper, a quality comparison of protein crystals which were grown under three containerless conditions provided by diamagnetic levitation, silicone oil and agarose gel was conducted. A control experiment on a vessel wall was also simultaneously carried out. Seven different proteins were crystallized under the four conditions, and the crystal quality was assessed in terms of the resolution limit, the mosaicity and the Rmerge. It was found that the crystals grown under the three containerless conditions demonstrated better morphology than those of the control. X‐ray diffraction data indicated that the quality of the crystals grown under the three containerless conditions was better than that of the control. Of the three containerless crystallization techniques, the diamagnetic levitation technique exhibited the best performance in enhancing crystal quality. This paper is to our knowledge the first report of improvement of crystal quality using a diamagnetic levitation technique. Crystals obtained from agarose gel demonstrated the second best improvement in crystal quality. The study indicated that the diamagnetic levitation technique is indeed a favourable method for growing high‐quality protein crystals, and its utilization is thus potentially useful in practical efforts to obtain well diffracting protein crystals.